Modern Approaches in Management of Children with Cystic fibrosis - Alexander A. Baranov; Leyla S. Namazova-Baranova; Sergey I. Kutsev; Sergey N. Avdeev; Elena V. Polevichenko; Andrey S. Belevskiy; Elena I. Kondratyeva; Olga I. Simonova; Nataliya Yu. Kashirskaya; Victoria D. Sherman; Anna Yu. Voronkova; Evgeniya L. Amelina; et al. (Педиатрическая фармакология)
The problem of timely diagnosis and proper management of patients with cystic fibrosis is crucial not only in our country, but throughout the world. Experts of the Union of Pediatricians of Russia have considered various issues of etiology, pathogenesis, epidemiology, diagnosis, and treatment of this genetic disease in a modern light. Particular attention was paid to screening methods for early diagnosis of cystic fibrosis. The principles of complex therapy were justified, including rational use of antibacterial and mucolytic drugs and enzyme replacement therapy that significantly determine the disease prognosis.